2010
DOI: 10.1007/s00484-010-0340-2
|View full text |Cite
|
Sign up to set email alerts
|

Weather daily variation in winter and its effect on behavior and affective states in day-care children

Abstract: This study aimed to analyze the impact of winter weather conditions on young children's behavior and affective states by examining a group of 61 children attending day-care centers in Florence (Italy). Participants were 33 males, 28 females and their 11 teachers. The mean age of the children at the beginning of the observation period was 24.1 months. The day-care teachers observed the children's behavioral and emotional states during the morning before their sleeping time and filled in a questionnaire for each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 35 publications
(47 reference statements)
1
13
0
1
Order By: Relevance
“…A study conducted in Finland found that activity level is linked to day length: longer days are associated with increased mean total day activity levels [ 51 ]. Interestingly, solar radiation was one of the main predictors of children’s emotional and behavioral states in day-care centers in Florence, Italy [ 52 ]. Daylight length variation has been suggested as one of the variables that may affect seasonal differences in growth [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Finland found that activity level is linked to day length: longer days are associated with increased mean total day activity levels [ 51 ]. Interestingly, solar radiation was one of the main predictors of children’s emotional and behavioral states in day-care centers in Florence, Italy [ 52 ]. Daylight length variation has been suggested as one of the variables that may affect seasonal differences in growth [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The solution to reducing playground heat illness and surface burns on extreme heat days is not to prohibit play, but to encourage safe play, invoke awareness, and/or limit play to the morning or evening hours. Quality play settings result in increased activity and improved health (e.g., lessen obesity and diabetes) (Barnes, 2011) and social networking (Bessesen, 2008;Sallis, Floyd, Rodríguez, & Saelens, 2012;Wolch et al, 2011), increased cognitive and motor development (Boldemann et al, 2006;Brussoni, Olsen, Pike, & Sleet, 2012;Ciucci et al, 2011Ciucci et al, , 2013Wenner, 2009), and improved behavior (Bessesen, 2008;Ciucci et al, 2013;Lagacé-Séguin & d'Entremont, 2005) and learning (Taylor & Kuo, 2009). Quantifying both the T s-a over various surfaces and the scale offsets of these deltas can produce accurate and vital information for reducing playground T s through bioclimatic design.…”
Section: Health and Safety Standards In Playgrounds Related To Tempermentioning
confidence: 99%
“…Some researchers have argued that rainfall is related to civil conflict through agricultural production (Miguel et al, 2004;Miguel and Satyanath, 2011;Maystadt and Ecker, 2014;Couttenier and Soubeyran, 2014). Alternatively, rainfall could have direct psychological effects on combatants, or be related to civil conflict through its impact on roads, bridges and the availability of surface water (Witsenburg and Adano, 2013;Ciucci et al, 2011;Hiltunen et al, 2012;Sarsons, 2013;Hsiang and Burke, 2014). 1 1 After studying pastoralists and farmers from northern Kenya for several years, Witsenburg and Adano (2009, p. 520) …”
Section: Introductionmentioning
confidence: 99%